2015
DOI: 10.1371/journal.pone.0119980
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Role of Interleukin 6 Receptor Haplotypes in the Regulation of Circulating Levels of Inflammatory Biomarkers and Risk of Coronary Heart Disease

Abstract: Variants at the interleukin 6 receptor (IL6R) gene regulate inflammation and are associated with risk of coronary heart disease (CHD). The aim of the present study was to investigate the effects of IL6R haplotypes on circulating levels of inflammatory biomarkers and risk of CHD. We performed a discovery analysis in SHEEP, a myocardial infarction (MI) case control study (n = 2,774) and replicated our results in two large, independent European populations, PROCARDIS, a CHD case control study (n = 7,998), and IMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 30 publications
(49 reference statements)
2
23
0
1
Order By: Relevance
“…Of note, it has been demonstrated that SNPs in the IL6R gene (e.g., Asp358Ala [rs2228145]; ref. 33) can influence inflammation in the context of various inflammatory (34)(35)(36) and cardiac disorders (37)(38)(39). In summary, these findings offer insights into the role of the ectopic membrane-bound IL6R upregulation in PA-SMCs in PAH.…”
Section: Discussionmentioning
confidence: 79%
“…Of note, it has been demonstrated that SNPs in the IL6R gene (e.g., Asp358Ala [rs2228145]; ref. 33) can influence inflammation in the context of various inflammatory (34)(35)(36) and cardiac disorders (37)(38)(39). In summary, these findings offer insights into the role of the ectopic membrane-bound IL6R upregulation in PA-SMCs in PAH.…”
Section: Discussionmentioning
confidence: 79%
“…He contributed to the development of the first antibody against the IL‐6 receptor (tocilizumab) for the treatment of rheumatic arthritis. Subsequent research determined that IL‐6 is also closely related to diseases such as coronary heart disease, schizophrenia, and gestational diabetes mellitus . Recent studies have found that IL‐6 is closely linked to the biogenesis and growth of tumors, including those of breast cancer, myeloma, and lung cancer.…”
Section: Pathological Activity Of Il‐6mentioning
confidence: 99%
“…This is well represented by coronary heart disease and atherosclerosis in which the genetic predisposition is largely based on IL6 receptor polymorphisms [136,137] and severity correlates with the extent and duration of chronic inflammation [138]. In general terms, we continue to affirm that the predisposition to complex diseases such as those based on autoimmunity and chronic inflammation is secondary to the coexistence of a permissive genetic background and specific environmental factors and MZ twins are excellent intuitive models to estimate these factors.…”
Section: Discussionmentioning
confidence: 98%